At the origin of the Christian claim - Giussani, Luigi (McGill-Queen's University Press, 1998)
Giussani argues that if we accept the hypothesis that the mystery entered the realm of human existence and spoke in human terms, the relationship between the individual and God is no longer based on a moral, imaginative, or aesthetic human effort but instead on coming upon an event in one's life. Thus the religious method is overturned by Christ: in Christianity it is no longer the person who seeks to know the mystery but the mystery that makes himself known by entering history. At the Origin of the Christian Claim presents an intriguing argument supported with ample documentation from the gospels and other theological writings.